PENGARUH PENDIDIKAN JASMANI DAN KESEHATAN GIZI PADA ANAK USIA DINI TERHADAP PENURUNAN ANGKA KEJADIAN STUNTING - Haeril Haeril (KORSA: Jurnal Kajian Ilmu Keolahragaan dan Kesehatan, 2023)
The aims of this research is to determine the level of knowledge of physical education and nutritional health education in Polman Regency. The research method used is survey or observation with a cross-sectional research design with a quantitative approach. The population in this study is the community or residents of Polman district with the research sample criteria being selected using the criteria 1) adult age; 2) have children at an early age; 3) can access questionnaires online and offline; and 4) willing to participate in research. Based on the research results, the level of physical education knowledge is 63% in the poor category, 33% in the medium category, and 3% in the good category. Meanwhile, the level of nutritional education knowledge was 83% in the poor category, 17% in the moderate category, and 0% in the good category.